THE PRACTICE OF SHARED VALUES AND ISLAMIC EDUCATIONAL IDENTITY: Evidence from a Pesantren in East Java, Indonesia - Kawakip, Akhmad Nurul; Sulanam, Sulanam (State Islamic University (UIN) of Sunan Ampel Surabaya, 2023)
This paper aims at exploring shared values in a traditional Islamic boarding school, Pesantren Sidogiri one of the oldest educational institutions in Indonesia, and their impact on the pesantren’s identity construction. Pesantren Sidogiri has been running for nearly three centuries with all of the distinctive characteristics and customs. Through ethnographic study this article seeks how the community in this particular pesantren engages with the educational system organised based on their shared values. The results demonstrate that the shared values preserved shape the identity of the traditional Islamic education institution namely persistent greater emphasis on Islamic teaching, moral development, and shared awareness not to depend on the states’ policies in two areas: teaching materials and funding.